Identification of Student Learning Style Preference Profiles in Hybrid Learning Settings: An Essential Consideration for Developing Learning Strategies - Aldinel Fikri; Kartika Nuradina (Westscience Press, 2023)
After Covid-19, several educational institutions have adopted the hybrid learning system. The transition of learning systems from face-to-face to hybrid settings presents obstacles and challenges that require adaptive solutions. The compatibility between hybrid learning systems and student learning style preferences is an issue that needs to be studied in more depth. Students have their preferred way when it comes to learning. They prefer to learn through visual (V), aural (A), read-write (R), or kinesthetic (K). Depending on their learning styles, student adaptation may have been challenging. In this regard, a study was designed to identify the learning style preferences among students. The VARK questionnaire is one of the most widely used diagnostic tools, allowing teachers to understand students' learning preferences and develop innovative learning practices. A quantitative cross-sectional design was conducted among students (n=486) in Univeristy X using the VARK questionnaire. Student learning style preferences were identified using latent profile analysis. Our findings suggest that most students were identified as having multiple learning modalities, while the rest had a single learning modality. Prevalence of kinesthetic and aural learning styles preference highest among students, followed by visual and read-write learning styles. Understanding how students retain the knowledge imparted to them is essential for lecturers to develop innovative and adaptive strategies.